Investigation of risk factors for pain chronification in patients suffering from infections of the spine - Zhao, Yina; Hemmer, Stefan; Pepke, Wojciech; Akbar, Michael; Schiltenwolf, Marcus; Dapunt, Ulrike A. (Journal of Clinical Medicine, 2020)
Background: Spinal infections represent a therapeutic challenge. The often protracted course of the disease is accompanied by pain, which can lead to a chronic pain experience even after the infectious disease has been treated successfully. The aim of this study was to investigate possible risk factors of pain chronification. Methods: In a prospective study, 14 patients with spinal infections were examined at admission (T1), at discharge from inpatient therapy (T2), and three to eight months postoperatively (T3) byquestionnaires on risk factors for pain chronification and by quantitative sensory testing (QST). Results: In-patient treatment lasted on average 45.3 days (±33.13). The patients complained of pain for 3.43 months (±2.77) prior to inpatient treatment. The visual analogue scale (VAS) for pain (0-10) and the Oswestry Disability Index detected significant improvement in the course of the study. However, patients also reported catastrophic thinking, as well as fear of movement and (re)-injury. Conclusion: In summary, our results demonstrate that patients with spinal infections did not suffer from pain chronification, but might benefit from an interdisciplinary therapeutic approach, which emphasizes promoting active pain-coping strategies, as well as addressing fear of movement and catastrophic thinking.